Siberian genetic diversity reveals complex origins of the Samoyedic‐speaking populations. Issue 6 (8th November 2018) - Karafet, Tatiana M.; Osipova, Ludmila P.; Savina, Olga V.; Hallmark, Brian; Hammer, Michael F.
Abstract: Objectives: We examined autosomal genome‐wide SNPs and Y‐chromosome data from 15 Siberian and 12 reference populations to study the affinities of Siberian populations, and to address hypotheses about the origin of the Samoyed peoples. Methods: Samples were genotyped for 567 096 autosomal SNPs and 147 Y‐chromosome polymorphic sites. For several analyses, we used 281 093 SNPs from the intersection of our data with publicly available ancient Siberian samples. To examine genetic relatedness among populations, we applied PCA, F ST, TreeMix, and ADMIXTURE analyses. To explore the potential effect of demography and evolutionary processes, the distribution of ROH and IBD sharing within population were studied. Results: Analyses of autosomal and Y‐chromosome data reveal high differentiation of the Siberian groups. The Siberian populations have a large proportion of their genome in ROH and IBD segments. Several populations (ie, Nganasans, Evenks, Yukagirs, and Koryaks) do not appear to have experienced admixture with other Siberian populations (ie, producing only positive f3), while for the other tested populations the composition of mixing sources always included Nganasans or Evenks. The Nganasans from the Taymyr Peninsula demonstrate the greatest level of shared shorter ROH and IBD with nearly all other Siberian populations. Conclusions: Autosomal SNP and Y‐chromosome data demonstrate that Samoyedic populations differ significantly in their genetic composition. Genetic relationship is observed only between Forest and Tundra Nentsi. Selkups are affiliated with the Kets from the Yenisey River, while the Nganasans are separated from their linguistic neighbors, showing closer affinities with the Evenks and Yukagirs.